1987
DOI: 10.1002/clc.4960101202
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and elimination of heart arrhythmias by adaptation to intermittent high altitude hypoxia

Abstract: Summary:It was shown that adaptation to intermittent hypoxia in altitude chamber prevented the poststress fall of the electrical threshold of heart fibrillation. In acute ischemia, the number of fibrillation episodes and the death rate of preadapted animals were 2-3 fold lower than in controls. The adaptation to hypoxia resulted in a significant increase in concentration of opioid peptide pendorphin in adrenal glands while stress-induced changes in 0-endorphin in brain structures of adapted animals were much l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 14 publications
3
50
0
1
Order By: Relevance
“…Previous investigators have shown that intermittent hypoxia could protect against ischemia/ reperfusion injury [4][5][6]11], but no measure of apoptosis has been reported. Another finding in our study is that the antiapoptotic effect of intermittent hypoxia was due to regulate expression of Bcl-2/Bax protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigators have shown that intermittent hypoxia could protect against ischemia/ reperfusion injury [4][5][6]11], but no measure of apoptosis has been reported. Another finding in our study is that the antiapoptotic effect of intermittent hypoxia was due to regulate expression of Bcl-2/Bax protein.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that intermittent hypoxia might have the cardioprotective effects similar to those observed in ischemic preconditioning [2][3][4][5][6][7][8]. A number of studies have attempted to define the mechanisms of this phenomenon and several potential factors have been proposed to be involved in the protective mechanism afforded by intermittent hypoxia [3,[5][6][7][9][10][11], however, the precise mechanisms underlying the protective effects of intermittent hypoxia on ischemic hearts are far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…contractile dysfunction (3,33), arrhythmias (31,52), and cell death (8,27). Recently, we (48) revealed a therapeutic effect of IHH on permanent coronary artery ligation-induced myocardial infarction by attenuating infarct size, myocardial fibrosis, and apoptosis and improving cardiac performance.…”
mentioning
confidence: 99%
“…These findings indicate that IHA hypoxia mitigates I/R-induced depression in SR Ca 2ϩ -pump ATPase activity by upregulating dual-site PLB phosphorylation, which may consequently contribute to IHA hypoxia-induced cardioprotection against I/R injury. phospholamban phosphorylation residues; cardiac sarcoplasmic reticulum Ca 2ϩ -pump ATPase; cardiac contractile function ADAPTATION TO INTERMITTENT HIGH-ALTITUDE (IHA) hypoxia increases cardiac tolerance to subsequent severe hypoxic or ischemic injury in animal models (1,17,24,26,37). Some clinical and epidemiological observations also have shown that the cardiac tolerance to acute oxygen deprivation is increased and that the incidence of myocardial infarction and mortality from coronary heart disease is reduced in people living at high altitude (8).…”
mentioning
confidence: 99%